Doncaster Mansion House Portraits: A Pictorial Tour. (23rd September 2022) - Barber, Brian
Abstract: Doncaster's civic Mansion House contains, amongst other paintings, 23 portraits in oils acquired between 1804 and 1985 in four of its principal rooms. A few were commissioned for the building, but most were obtained by gift from a range of donors. This article explains the occasion and examines the motives for these acquisitions and suggests some mutual features which provide historical links between them.